Industrial Robotic Automation: Motivational Drivers and Safety Considerations for Implementation and Use - (:unkn) unknown (My University, 2025)
Part 1: Industry 4.0 has brought forward a new type of robot, a cobot, designed to interact with humans during manufacturing processes. Cobots are precise, efficient, and do not require distance or physical barriers from the employees they work with and around. The emerging technology introduces hazards distinct from those associated with traditional industrial robotics, yet there is limited evidence to suggest that safety control protocols have been adapted to address these differences. In order to assess how safety measures have evolved with the advent of this technology, a comprehensive literature review was performed to identify the key factors contributing to human-cobot collisions resulting in injuries within general manufacturing. The study includes an evaluation on collision detection and avoidance technology as well as commentary on specific standards aimed to control cobot-human interaction safety. Over 200 research papers and/or books covering topics on robotic knowledge, procurement motivation, implementation, training, and safety were examined. Inclusion criteria, defined by quality of work and its applicability, were utilized to identify research efforts warranting further study. In addition, safety standards were examined, with a focus on general robotics and robotic safety in particular. Modern robotic technology incorporates both proprioceptive and exteroceptive sensors, as well as control system algorithms designed for pre-collision detection, collision identification, and collision avoidance. Robotic safety standards are currently beginning developed and made available for use, however, no mandatory regulations have been established in the United States at this time. Established and historically effective training methodologies continue to be applied. While advancements in cobot technology show promise, there remains a significant need for more precise and reliable sensory system and control algorithms. At present, most technological innovations struggle to manage the complexity of dynamic and densely populated workstations. To enhance robotic safety, standards must become more tailored to specific robot types and applications while aligning with manufacturing needs and practical considerations. Establishing a standard outlining the processes and requirements for introducing new safety advancements to market could prove beneficial for both manufacturers and customers. Tailored training programs, designed to address specific topics and adapted to individual users, are necessary for flawless implementation. However, the pace of technological advancements and standard development is lagging behind the rapid adoption of cobot technologies. Relying solely on past safety practices is not enough to prevent injuries and incidents. Technological innovation should be driven by the needs of the manufacturing sector, and safety standards must be developed to ensure that newly validated safety measures are integrated into products and applied during operation. In addition, providing customers with comprehensive guidelines for proper training and implementation can promote best practices, fostering a safer work environment for everyone. Part 2: Integrating robotics into industrial operations is generally believed to enhance productivity, lower costs, and improve occupational health and safety. These anticipated advantages are considered key factors motivating companies to adopt robotic solutions in their manufacturing processes. While robotics introduce distinct risks compared to manual labor, they hold potential to positively alter company safety outcomes for businesses. Limited research has been conducted to identify the key factors influencing companies’ decisions to adopt industrial robotics. Moreover, the question of how the motivational factors differ between companies based on their type or size for example, remains insufficiently explored. A study was conducted to examine distinctions in motivations for robotization, focusing specifically on safety-related aspects. The investigation compared companies with existing robotic processes (robotic companies) to those without such systems (non-robotic companies). Among the latter, further differentiation was made between companies planning to implement robotics in the future and those with no plans to do so. A custom designed and validated survey was administered, gathering data from 100 companies within the general manufacturing sector, 52 of which currently utilize robotics. Statistically significant differences in motivational factors were observed across robotic companies, those planning to adopt robotics, and those with no plans to do so. Economic aspects emerged as the primary justification for adopting robotics across all company types. Additionally, differences in perceived safety hazards and injury types were identified between robotic and non-robotic companies. Robotics showcase the potential to mitigate certain hazard types, yet they may also pose risks to employees if not properly implemented. Companies, irrespective of their size or geographic location, hold varying views on the motivation behind and safety implications of industrial robotization, depending on whether they currently utilize robotic systems or not.
Keywords: Industrial engineering; Collaborative Human-robot Interaction; Occupational Safety; Robotic Automation; Robotic Collision Detection Technology